2022
DOI: 10.3390/ijerph192316307
|View full text |Cite
|
Sign up to set email alerts
|

Does the Intensity of the Headache Differ According to the Level of Neck Disability in Chronic Migraine Patients?

Abstract: Chronic migraine (CM) patients who report a high frequency and intensity of headaches also report neck pain (NP) and neck disability (ND) in neck activities that require stability. In this context, CM patients may report different headache intensities at different levels of ND. Our aim in this study is to investigate whether the intensity of headaches differs according to the level of ND in CM patients. Headache intensity and NP intensity were evaluated with the Visual Analog Scale (VAS), and ND was evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Di Antonio et al showed that in migraine patients with NP, the cervical active range of motion was less than in migraine patients without neck pain, the headache frequency was higher, the disability was worse, and the pain threshold in the cervical region was also lower [ 29 ]. In the previous clinical study, it was stated that an average of 2 cm increase in the intensity of headache at the mild neck disability level progressed to the complete neck disability, while an average 1 cm increase in the intensity of headache at the moderate neck disability level also progressed to the complete neck disability level [ 20 ]. Therefore, based on the results of clinical studies, when migraine attacks are considered, it can be understood that the increase in the headache frequency, the intensity of headaches, and the number of monthly painful days can negatively affect neck disability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Di Antonio et al showed that in migraine patients with NP, the cervical active range of motion was less than in migraine patients without neck pain, the headache frequency was higher, the disability was worse, and the pain threshold in the cervical region was also lower [ 29 ]. In the previous clinical study, it was stated that an average of 2 cm increase in the intensity of headache at the mild neck disability level progressed to the complete neck disability, while an average 1 cm increase in the intensity of headache at the moderate neck disability level also progressed to the complete neck disability level [ 20 ]. Therefore, based on the results of clinical studies, when migraine attacks are considered, it can be understood that the increase in the headache frequency, the intensity of headaches, and the number of monthly painful days can negatively affect neck disability.…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of a hospital-based clinical study, an average 2 cm increase in headache intensity in CM patients with mild neck disability in the NDI could result in complete neck disability. In CM patients with moderate neck disability levels, it has been found that an average 1 cm increase in headache intensity can cause complete neck disability [ 20 ]. Therefore, evaluating patients in clinics in terms of neck disability may shed light on how much changes in headache intensity may affect neck disability.…”
Section: Introductionmentioning
confidence: 99%
“…The headache disability inventory (HDI) [ 18 ] measured 28% at initial evaluation. His initial neck disability index (NDI) [ 19 ] measured 26% indicating mild to moderate disability due to neck pain. He reported low back pain intermittently in the mid lumbar spine with a modified Oswestry disability index (MODI) [ 20 ] measuring 22% indicative of moderate disability due to pain.…”
Section: Case Presentationmentioning
confidence: 99%
“…Notably, the presence of neck pain during migraine attacks is associated with increased disease burden. Neck pain and disability due to neck pain (referred to as neck disability) are correlated with higher headache frequency, 9,11 and a relatively small increase in headache pain intensity in people who report mild disability due to neck pain during migraine can lead to complete neck disability (i.e., severe impairment in areas such as concentration, sleep, and daily activities) 12 . In addition, neck pain is associated with a higher prevalence of cutaneous allodynia, 5 a risk factor for migraine progression and inadequate response to acute therapy 13,14 …”
Section: Introductionmentioning
confidence: 99%